Perlite-based cementitious materials, concrete, and related technologies

JP2024525671A5Pending Publication Date: 2025-02-26ECO MATERIAL TECH IP INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024501199
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-02-10
Filing Date
2022-02-15
Publication Date
2025-02-26

AI Technical Summary

Technical Problem

Perlite has limited practicality as a substitute for ordinary Portland cement due to its high water consumption and low reactivity, resulting in concrete with significantly lower initial compressive strength.

Method used

A treated perlitic cementitious mixture is created by intermilling perlite coarse ore with polyvinyl alcohol (PVA) powder, polycarboxylate material, and optionally calcium sulfate and calcium sulfite, achieving a D90 particle size distribution of 28-38 μm, which is then combined with ordinary Portland cement, sand, and water to form concrete.

Benefits of technology

The treated perlitic cementitious mixture enhances the reactivity of perlite, reduces water consumption, and improves compressive strength, achieving results comparable to or exceeding those of conventional OPC-based concrete, while maintaining a lightweight nature.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

Treated perlitic cementitious materials, concrete, and related techniques are disclosed. According to some embodiments, the treated perlitic cementitious materials may be made by inter-grinding perlite crud, polyvinyl alcohol (PVA) powder, polycarboxylate material, and (optionally) at least one of calcium sulfate (CaSO4) and calcium sulfite (CaSO3). According to some embodiments, the cementitious materials may also include expanded perlite waste and / or expanded perlite. According to some embodiments, the perlite crud, expanded perlite waste, and expanded perlite may be combined in providing the cementitious materials. In at least some cases, the cementitious materials may be provided as a mix where the powders are all mixed together. According to some embodiments, concrete may be made by mixing the cementitious materials with ordinary Portland cement (OPC), sand, rock, and water.
Need to check novelty before this filing date? Find Prior Art

Description

Detailed Description of the Invention

[0001] [CROSS REFERENCE TO RELATED APPLICATIONS] This patent application claims the benefit of (1) U.S. Provisional Patent Application No. 63 / 220392, filed July 9, 2021, (2) U.S. Provisional Patent Application No. 63 / 244447, filed September 15, 2021, and (3) U.S. Provisional Patent Application No. 63 / 308566, filed February 10, 2022. Each of these applications is incorporated herein by reference in its entirety.

[0002] [Technical field] The present disclosure relates to cementitious materials, and in particular to perlite-based cementitious materials, concrete, and techniques.

[0003] [Background technology] Perlite is a naturally occurring amorphous obsidian, typically consisting of about 70-75% silicon dioxide, 12-15% aluminum oxide, 3-5% potassium oxide, 3-4% sodium oxide, and trace amounts of iron oxide, magnesium oxide, and calcium oxide. Over time, the matrix of perlite ore absorbs water. Because of its high water content, perlite expands significantly when heated sufficiently. Typically, perlite "foams" when heated above about 1,300 °F. The resulting expanded perlite is remarkably lightweight and absorbent.

[0004] [Summary of the invention] The subject matter of this application may, in some cases, include interrelated products, alternative solutions to a particular problem, and / or different uses of a single system or article.

[0005] An exemplary embodiment provides a method for making a treated perlite-based cementitious mixture that includes perlite, polyvinyl alcohol (PVA) powder, and a polycarboxylate material. In some cases, the perlite is perlite crude.

[0006] In some cases, preparing the treated perlitic cementitious mixture includes intergrinding the perlite crude, the PVA powder, and the polycarboxylate material. In some such cases, the intergrinding is performed until a D90 particle size distribution of about 38 μm is achieved for the treated perlitic cementitious mixture. In some other such cases, the intergrinding is performed until a D90 particle size distribution of about 28 μm is achieved for the treated perlitic cementitious mixture.

[0007] In some cases, the treated perlitic cementitious mixture further comprises at least one of calcium sulfate (CaSO4) and calcium sulfite (CaSO3). In some such cases, making the treated perlitic cementitious mixture comprises inter-grinding perlite crude, PVA powder, polycarboxylate material, and at least one of calcium sulfate and calcium sulfite.

[0008] In some cases, the treated perlitic cementitious mixture further comprises at least one of expanded perlite waste and expanded perlite. In some such cases, producing the treated perlitic cementitious mixture comprises inter-grinding the perlite crumble, the PVA powder, the polycarboxylate material, and at least one of the expanded perlite waste and expanded perlite.

[0009] In some cases, the treated perlitic cementitious mixture further comprises expanded perlite waste and expanded perlite. In some such cases, making the treated perlitic cementitious mixture comprises inter-grinding the perlite crude, the PVA powder, the polycarboxylate material, the expanded perlite waste, and the expanded perlite.

[0010] Another exemplary embodiment provides a method for making concrete comprising a treated perlitic cementitious mixture made as described above, ordinary Portland cement (OPC), water, and at least one of rock and sand. In some cases, the treated perlitic cementitious mixture and the OPC are provided in a 50:50 mix. Another exemplary embodiment provides a concrete product comprising the concrete made as described above.

[0011] Another exemplary embodiment provides a composition. The composition includes perlite, polyvinyl alcohol (PVA) powder, and a polycarboxylate material. In some cases, the perlite is perlite crude. In some cases, the composition has a D90 particle size distribution of about 38 μm. In some cases, the composition has a D90 particle size distribution of about 28 μm. In some cases, the composition further includes at least one of calcium sulfate (CaSO4) and calcium sulfite (CaSO3). In some of the above cases, the composition further includes at least one of expanded perlite waste and expanded perlite. In some of the above cases, the composition further includes expanded perlite waste and expanded perlite. In some of the above cases, the composition further includes ordinary Portland cement (OPC).

[0012] The features and benefits described herein are not all-inclusive, and numerous additional features and benefits will become apparent to those skilled in the art, particularly upon review of the drawings, specification, and claims.Furthermore, it should be noted that the terminology used within this specification has been selected primarily for ease of reading and educational purposes, and is not intended to limit the scope of the inventive subject matter.

[0013] These and other features of the embodiments will be better understood from the following detailed description taken in conjunction with the drawings described herein. In the drawings, identical or nearly identical components shown in various figures may be represented by similar reference numerals. For clarity, not all components have been referenced in each figure. Moreover, as will be appreciated in light of the present disclosure, the accompanying drawings are not drawn to scale, nor are they intended to limit the described embodiments to the particular configurations illustrated. [Brief description of the drawings]

[0014] [Figure 1] FIG. 1 illustrates a method of making a treated perlitic cementitious material according to an embodiment of the present disclosure. [Diagram 2] FIG. 2 illustrates a method of making concrete according to an embodiment of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] [Detailed Description of the Invention] Treated perlitic cementitious materials, concrete, and related techniques are disclosed. According to some embodiments, the treated perlitic cementitious materials may be made by inter-grinding perlite crud, polyvinyl alcohol (PVA) powder, polycarboxylate material, and (optionally) at least one of calcium sulfate (CaSO4) and calcium sulfite (CaSO3). According to some embodiments, the cementitious materials may also include expanded perlite waste and / or expanded perlite. According to some embodiments, the perlite crud, expanded perlite waste, and expanded perlite may be combined in providing the cementitious materials. In at least some cases, the cementitious materials may be provided as a mix in which the powders are all mixed together. According to some embodiments, concrete may be made by mixing the cementitious materials with ordinary Portland cement (OPC), sand, rock, and water. Numerous configurations and variations will become apparent in view of the present disclosure.

[0016] [Overview] Perlite has had limited utility as a substitute for ordinary Portland cement (OPC) due to its high water consumption when mixed with water. This is due, at least in part, to the limited reactivity of the amorphous glass of the crude ore, which is due to the high silicate content but very little calcium present in the glass. As a result, concrete made with perlite usually has dramatically lower early compressive strength than typical OPC-based concretes.

[0017] Thus, according to some embodiments of the present disclosure, a treated perlite-based cementitious material, concrete, and related techniques are disclosed. According to some embodiments, the treated perlite-based cementitious material may be made by inter-grinding perlite crud, polyvinyl alcohol (PVA) powder, polycarboxylate material, and (optionally) at least one of calcium sulfate (CaSO4) and calcium sulfite (CaSO3). According to some embodiments, the cementitious material may also include expanded perlite waste and / or expanded perlite. According to some embodiments, the perlite crud, expanded perlite waste, and expanded perlite may be combined in providing the cementitious material. In at least some cases, the cementitious material may be provided as a mix where the powders are all mixed together. According to some embodiments, concrete may be made by mixing the cementitious material with OPC, sand, rock, and water.

[0018] As can be appreciated in light of this disclosure, the technology disclosed herein can be utilized in any of a wide variety of situations and applications, such as horticulture, shielding, fill, ceiling tile masonry, mortar, among others.

[0019] [Treated perlitic cementitious material] FIG. 1 illustrates a method 1000 for making a treated perlite-based cementitious material according to certain embodiments of the present disclosure. As can be seen, the method 1000 may add perlite ore, as shown in block 1002. As can be seen in light of the present disclosure, the perlite ore may be sourced as desired for a given intended use or end demand. According to some embodiments, the perlite ore may be (or may include) perlite available from Imerys USA, Inc. According to some embodiments, the perlite ore may be (or may include) DICAPERL® perlite available from Dicalite Management Group. The amount of perlite ore added may be tailored as desired for a given intended use or end demand. According to some embodiments, perlite crude may comprise about 25-50 wt% (e.g., about 25-30 wt%, about 30-35 wt%, about 35-40 wt%, about 40-45 wt%, about 45-50 wt%, or any other subrange within about 25-50 wt%) of a given mixture made according to method 1000. Other suitable types and amounts of perlite will be apparent in light of this disclosure.

[0020] Method 1000 may add polyvinyl alcohol (PVA) powder, as shown in block 1004. The amount of PVA powder may be tailored as desired for a given intended use or end need. According to some embodiments, the PVA powder may comprise about 0.1-0.4 wt% (e.g., about 0.1-0.15 wt%, about 0.15-0.2 wt%, about 0.2-0.25 wt%, about 0.25-0.3 wt%, about 0.3-0.35 wt%, about 0.35-0.4 wt%, or any other subrange within the range of about 0.1-0.4 wt%) of a given mixture made according to method 1000. Other suitable amounts of PVA powder will be apparent in light of the present disclosure.

[0021] The method 1000 may add one or more polycarboxylate materials, as shown in block 1006. In general, the polycarboxylate materials may be any of a variety of polycarboxylate heteropolymer or copolymer (i.e., two monomer) materials. According to some embodiments, the polycarboxylate materials may be superplasticizers. In some cases, one polycarboxylate material may be used, or a combination of two or more different polycarboxylate materials may be used. In at least some cases, it may be desirable for the polycarboxylate material(s) to be in powder form, although this is not required. The amount of polycarboxylate material(s) added may be tailored as desired for a given intended use or end need. According to some embodiments, the polycarboxylate material(s) may comprise about 0.1-0.3 wt% (e.g., about 0.1-0.15 wt%, about 0.15-0.2 wt%, about 0.2-0.25 wt%, about 0.25-0.3 wt%, or any other subrange within the range of about 0.1-0.3 wt%) of a given mixture made according to method 1000. Other suitable amounts of the polycarboxylate material(s) will be apparent in light of the present disclosure.

[0022] According to certain exemplary embodiments, the polycarboxylate material may be a polycarboxylate copolymer described as a superplasticizer, such as Polycarboxylate-PCX CAS No. 59233-52-2 available from WEGO Chemical and Mineral Corporation, Great Neck, NY (hereinafter WEGO Polycarboxylate-PCX), which has the following general chemical structure: where (1) M, Y, and X are leaving groups; (2) R 1 ~R 4is an aliphatic carbon chain, (3) ethylene oxide (EO) is a hydrophilic component, and (4) propylene oxide (PO) is a hydrophobic component.

[0023] [ka]

[0024] The hydrophilic EO component of WEGO Polycarboxylate-PCX has the following chemical structure:

[0025] [ka]

[0026] In addition, the hydrophobic PO component of WEGO Polycarboxylate-PCX has the following chemical structure.

[0027] [ka]

[0028] For WEGO Polycarboxylate-PCX, the variables a, b, c, and n may be whole integers greater than or equal to 1, and the carbon bonds omitted from the illustrated chemical structure of WEGO Polycarboxylate-PCX may be bonded to hydrogen (H). It should further be noted that the leaving groups M, Y, and X are proprietary components not known outside of WEGO Chemical and Mineral Corporation. Nevertheless, without knowledge of the leaving groups M, Y, and X, one of ordinary skill in the art can utilize the techniques disclosed herein, including utilizing WEGO's commercially available Polycarboxylate-PCX, to make products as variously described herein in accordance with some embodiments of the present disclosure. It should also be noted that in accordance with some embodiments, one or more polycarboxylate materials of similar chemistry to WEGO Polycarboxylate-PCX may be utilized in addition to or in place of the leaving groups.

[0029] According to some embodiments, method 1000 may optionally add at least one of calcium sulfate (CaSO4) and calcium sulfite (CaSO3), as shown in block 1008. The amount of sulfate / calcium sulfite may be tailored as desired for a given intended use or end need. According to some embodiments, calcium sulfate (CaSO4) may comprise about 0.1-1.5 wt% (e.g., about 0.1-0.5 wt%, about 0.5-1 wt%, about 1-1.5 wt%, or any other subrange within the range of about 0.1-1.5 wt%) of a given mixture made according to method 1000. According to some embodiments, calcium sulfite (CaSO3) may comprise about 1.5-3 wt% (e.g., about 1.5-2 wt%, about 2-2.5 wt%, about 2.5-3 wt%, or any other subrange within the range of about 1.5-3 wt%) of a given mixture made according to method 1000. Other suitable amounts of calcium sulfate (CaSO4) and calcium sulfite (CaSO3) will be apparent in light of this disclosure.

[0030] Method 1000 may include inter-grinding (1) perlite crude, (2) PVA powder, (3) polycarboxylate material (or polycarboxylate materials), and (optionally) (4) calcium sulfate and / or calcium sulfite, as shown in block 1010. According to some embodiments, a processed perlitic cementitious material may be obtained by inter-grinding the aforementioned materials with each other (e.g., all at once or with one or more intermediate combinations).

[0031] As will be apparent in light of the present disclosure, the inter-grinding may be performed using any suitable grinding means. For example, according to some embodiments, the inter-grinding may be performed in part or in whole using a mill with grinding aids and mediators. The particular type of mill may be tailored as desired for a given intended use or end need. In some cases, the mill may be a rotary mill, such as a ball mill. According to some embodiments, the inter-grinding may be performed in part or in whole using a mill configured as disclosed in U.S. Pat. No. 9,254,490 ("Process for Treating Fly Ash and a Rotary Mill Therefor"), the entire contents of which are incorporated herein by reference. According to some embodiments, the inter-grinding may be performed with grinding aids and mediators configured as disclosed in U.S. Pat. No. 9,254,490.

[0032] The inter-grinding time of the materials involved in method 1000 may be tailored as desired for a given intended application or end need. For example, according to some embodiments, the inter-grinding may be performed for about 1-15 minutes. According to some embodiments, the inter-grinding may be performed for about 3-8 minutes. As will be appreciated in light of the present disclosure, at least in some cases, the inter-grinding of the materials may be performed, for example, until a predetermined target particle size distribution is achieved. For example, in some cases, the inter-grinding may be performed until a D90 particle size distribution in the range of about 20-40 μm (e.g., about 20-25 μm, about 25-30 μm, about 30-35 μm, about 35-40 μm, or any other subrange within the range of about 20-40 μm) is achieved. In some cases, the inter-grinding may be performed until a D90 particle size distribution of about 38 μm (± 3 μm) is achieved. In some cases, the inter-grinding may be performed until a D90 particle size distribution of about 28 μm (± 3 μm) is achieved. Other suitable milling times and target particle size distributions for materials associated with method 1000 will be apparent in light of this disclosure.

[0033] According to some embodiments, method 1000 may optionally add at least one of (1) expanded perlite waste (generated during the expansion of perlite crud to create "foamed" perlite) and (2) expanded perlite, as shown in block 1003. According to some embodiments, both expanded perlite waste and expanded perlite may be combined with the perlite crud. According to some embodiments, the expanded perlite may be (or may include) HARBORLITE® thermally expanded perlite available from Imerys, Inc., USA. Other suitable types of expanded perlite will be apparent in light of this disclosure.

[0034] The amount of expanded perlite shavings and / or expanded perlite may be tailored as desired for a given intended use or end need. According to some embodiments, the expanded perlite shavings may comprise about 6 wt% or less (e.g., about 1-2 wt%, about 2-3 wt%, about 3-4 wt%, about 4-5 wt%, about 5-6 wt%, or any other subrange within the range of about 6 wt% or less) of a given mixture made according to method 1000. According to some embodiments, the expanded perlite may comprise about 1 wt% or less (e.g., about 0.25-0.5 wt%, about 0.5-0.75 wt%, about 0.75-1 wt%, or any other subrange within the range of about 1 wt% or less) of a given mixture made according to method 1000. Other suitable amounts of expanded perlite shavings and expanded perlite will be apparent in light of the present disclosure.

[0035] In some cases, the expanded perlite waste and / or expanded perlite may be milled with PVA powder and one or more polycarboxylate materials in a mill (e.g., any of the mills described herein) and then mixed with finely ground perlite ore by co-grinding (e.g., for 1-5 minutes) in the mill. The additive (or additives) may be provided as a separate product that may be added to promote the reaction as described herein, according to some embodiments. According to some embodiments, the expanded perlite waste may be treated with an amount of PVA powder in the range of about 0.2 wt% or less (e.g., about 0.05-0.1 wt%, about 0.1-0.15 wt%, about 0.15-0.2 wt%, or any other subrange within the range of about 0.2 wt% or less). In some cases, the amount of PVA powder may be about 0.15 wt% ±0.05 wt%. Other suitable amounts of PVA powder for the treatment of expanded perlite waste will be apparent in light of the present disclosure.

[0036] [concrete] FIG. 2 illustrates a method 2000 for making concrete according to certain embodiments of the present disclosure. As can be seen, the method 2000 may add treated perlitic cementitious material made by the method 1000 (see FIG. 1 ), as shown in block 2002. The amount of cementitious material added in this manner may be tailored as desired for a given intended use or end need. According to some embodiments, the cementitious material may comprise about 25-50 wt% (e.g., about 25-30 wt%, about 30-35 wt%, about 35-40 wt%, about 40-45 wt%, about 45-50 wt%, or any other subrange within the range of about 25-50 wt%) of a given concrete made according to the method 2000. Other suitable amounts of cementitious material will be apparent in light of the present disclosure.

[0037] Method 2000 may add OPC, as shown in block 2004. The amount of OPC added may be tailored as desired for a given intended use or end need. According to some embodiments, the OPC may comprise about 25-50 wt% (e.g., about 25-30 wt%, about 30-35 wt%, about 35-40 wt%, about 40-45 wt%, about 45-50 wt%, or any other subrange within the range of about 25-50 wt%) of a given concrete made according to method 2000. According to some embodiments, the OPC and the treated perlitic cementitious material may be provided in a 50:50 powder mix ratio. Other suitable amounts of OPC will be apparent in light of this disclosure.

[0038] The method 2000 may add water and at least one of sand and rocks, as shown in block 2006. According to some embodiments, the sand may include sieve sand, for example, conforming to ASTM C989 standards. According to some embodiments, the rock material may include, for example, 3 / 4" limestone rock conforming to ASTM C33 standards. The amount of sand and / or rock added may be tailored as desired for a given intended use or end need. According to some embodiments, the sand may comprise about 45-55 wt% (e.g., about 45-50 wt%, about 50-55 wt%, or any other subrange within the range of about 45-55 wt%) of a given concrete made according to method 2000. According to some embodiments, the rock may comprise about 45-55 wt% (e.g., about 45-50 wt%, about 50-55 wt%, or any other subrange within the range of about 45-55 wt%) of a given concrete made according to method 2000. Other suitable types and amounts of sand and rock will be apparent in light of this disclosure.

[0039] The water-to-cement ratio (w / c) of concrete made according to method 2000 may also be tailored as desired for a given intended use or end need. In some cases, the w / c ratio may be within a range of about 0.2-0.4 (e.g., about 0.2-0.25, about 0.25-0.3, about 0.3-0.35, about 0.35-0.4, or any other subrange within the range of about 0.25-0.4). In some cases, the w / c ratio may be within a range of about 0.25-0.38 (e.g., about 0.25-0.31, about 0.31-0.38, or any other subrange within the range of about 0.25-0.38). In some cases, the w / c ratio may be within a range of about 0.2-0.33 (e.g., about 0.2-0.26, about 0.26-0.33, or any other subrange within the range of about 0.2-0.33). In some cases, the w / c ratio may be within the range of about 0.23 to 0.3 or 0.23 to 0.4. Other suitable w / c ratios for materials related to method 2000 will be apparent in light of this disclosure.

[0040] Method 2000 may include mixing (1) treated perlitic cementitious material, (2) OPC, (3) water, and / or (4) sand and / or rock, as shown in block 2008. According to some embodiments, concrete including treated perlitic cementitious material may be obtained by mixing the aforementioned materials with each other (e.g., all at once or with one or more intermediate combinations). Mixing may be performed as is typically done for concrete products. Additionally, mixing times for materials involved in method 2000 may be tailored as desired for a given intended use or end need. As will be appreciated in light of the present disclosure, it may be desirable to allow for shortened mixing times while still having sufficient supply time to cast, form, etc., the concrete as desired.

[0041] [Concrete batch example #1] In accordance with an exemplary embodiment, a first concrete batch example was prepared that included the following components: (1) treated perlitic cementitious material, (2) Type 1-2 OPC having a standard fineness distribution, (3) sieve sand conforming to ASTM C989 standards, and (4) water. The treated perlitic cementitious material was used at about 50 wt% replacement of the OPC.

[0042] The treated perlitic cementitious material described above is mixed with (1) perlite crude, (2) 0.15 wt% PVA powder, (3) 0.3 wt% WEGO Polycarboxylate-PCX, and (4) 0.05 wt% triethanolamine (TEA) grinding aid as follows: The perlitic cementitious material has a PSD with a D90 of 38 μm.

[0043] Table 1 below shows the measured compressive strength of several cubes of concrete hardened at ambient temperatures ranging from about 73°F (±3°F) under conditions conforming to ASTM C989. The compressive strength was determined by breaking the cubes.

[0044] [Table 1]

[0045] [Concrete batch example #2] According to an exemplary embodiment, a second concrete batch example was prepared that included the following components: (1) treated perlitic cementitious material, (2) Type 1-2 OPC with standard fineness distribution, (3) sieve sand conforming to ASTM C989 standard, and (4) water. The treated perlitic cementitious material was used at about 50 wt% replacement of the OPC.

[0046] The treated perlitic cementitious material described above is mixed with (1) perlite crude, (2) 0.15 wt% PVA powder, (3) 0.3 wt% WEGO Polycarboxylate-PCX, and (4) 0.05 wt% triethanolamine (TEA) grinding aid as follows: The perlitic cementitious material has a PSD with a D90 of 28 μm.

[0047] Table 2 below shows the measured compressive strength of several cubes of concrete hardened at ambient temperatures ranging from about 73° F. (± 3° F.) under conditions conforming to ASTM C989. The compressive strength was determined by breaking the cubes.

[0048] [Table 2]

[0049] [Concrete batch example #3] According to an exemplary embodiment, a third concrete batch example was prepared including the following components: (1) treated perlitic cementitious material, (2) Type 1-2 OPC having a standard fineness distribution, (3) sieve sand conforming to ASTM C989 standards, and (4) water. The treated perlitic cementitious material was used at about 50 wt% replacement of the OPC.

[0050] The treated perlitic cementitious material described above is mixed with (1) perlite crude, (2) 5 wt% class C fly ash, (3) 0.15 wt% PVA powder, (4) 0.3 wt% WEGO Polycarboxylate-PCX, and (5) 0.05 wt% triethanolamine (TEA) grinding aid. The perlitic cementitious material has a PSD with a D90 of 28 μm.

[0051] Table 3 below shows the measured compressive strength of several cubes of concrete hardened at ambient temperatures ranging from about 73° F. (± 3° F.) under conditions conforming to ASTM C989. The compressive strength was determined by breaking the cubes.

[0052] [Table 3]

[0053] [Concrete batch example #4] According to an exemplary embodiment, a fourth 5.02-sak concrete batch example was prepared including the following components: (1) treated perlitic cementitious material, (2) Type 1-2 OPC with standard fineness distribution, (3) 3 / 4″ limestone stone conforming to ASTM C33 standard, (4) sieve sand conforming to ASTM C989 standard, and (5) water. The treated perlitic cementitious material was used at about 50 wt% replacement of the OPC. The water to cement ratio (w / c) of this batch was 0.45.

[0054] The treated perlitic cementitious material described above is mixed as follows: (1) about 94.2 wt% perlite crude ore having a PSD of D90 of about 36 μm; (2) about 5 wt% expanded perlite fine scrap (derived from an expansion process on perlite raw ore) having a PSD of D90 of about 40 μm; (3) about 0.5 wt% expanded perlite having a PSD of D90 of about 25 μm; (4) about 0.05 wt% PVA powder; (5) about 0.2 wt% WEGO Polycarboxylate-PCX; and (6) about 0.05 wt% TEA grinding aid.

[0055] Table 4 below shows the measured compressive strength of several concrete cylinders hardened at ambient temperatures ranging from about 90°F (±3°F) under conditions conforming to ASTM C989. The compressive strength was determined by breaking the cylinders.

[0056] [Table 4]

[0057] [Concrete batch example #5] According to an exemplary embodiment, a fifth 5.02-sak concrete batch example was prepared including the following components: (1) treated perlitic cementitious material, (2) Type 1-2 OPC with standard fineness distribution, (3) 3 / 4″ limestone stone conforming to ASTM C33 standard, (4) sieve sand conforming to ASTM C989 standard, and (5) water. The treated perlitic cementitious material was used at about 50 wt% replacement of the OPC. The water to cement ratio (w / c) of this batch was 0.63.

[0058] The treated perlitic cementitious material described above is mixed as follows: (1) about 94.2 wt% perlite crude ore having a PSD of D90 of about 36 μm; (2) about 5 wt% expanded perlite fine scrap (derived from an expansion process on perlite raw ore) having a PSD of D90 of about 40 μm; (3) about 0.5 wt% expanded perlite having a PSD of D90 of about 25 μm; (4) about 0.05 wt% PVA powder; (5) about 0.2 wt% WEGO Polycarboxylate-PCX; and (6) about 0.05 wt% TEA grinding aid.

[0059] Table 5 below shows the measured compressive strength of several concrete cylinders hardened at ambient temperatures ranging from about 90°F (±3°F) under conditions conforming to ASTM C989. The compressive strength was determined by breaking the cylinders.

[0060] [Table 5]

[0061] [Concrete batch example #6] According to an exemplary embodiment, a sixth concrete batch example was prepared including the following components: (1) treated perlitic cementitious material, (2) Type 1-2 OPC having a standard fineness distribution, (3) sieve sand conforming to ASTM C989 standards, and (4) water. The treated perlitic cementitious material was used at about 50 wt% replacement of the OPC.

[0062] The above-mentioned treated perlitic cementitious material is mixed as follows: (1) about 93.5 wt% perlite crude ore having a PSD of D90 about 38 μm (e.g., available from Imerys, Inc., USA, sourced from Colorado); (2) about 6 wt% expanded perlite scrap having a PSD of D90 about 20 μm (e.g., available from Imerys, Inc., USA, sourced from Texas); (3) about 0.5 wt% expanded perlite having a PSD of D90 about 20 μm (e.g., HARBORLITE® thermally expanded perlite from Imerys). The expanded perlite scrap and expanded perlite were each treated with about 0.15 wt% PVA powder, about 0.3 wt% WEGO Polycarboxylate-PCX, and about 0.05 wt% TEA grinding aid. These materials are mixed together in a mill in proportions and milled (e.g., for about 20 minutes) to a PSD with a D90 of about 38 μm / kg with about 0.15 wt% PVA powder, about 0.3 wt% WEGO Polycarboxylate-PCX, and about 0.05 wt% TEA grinding aid.

[0063] Table 6 below shows the measured compressive strength of several cubes of concrete hardened under conditions conforming to ASTM C989 standard. The compressive strength was determined by breaking the cubes.

[0064] [Table 6]

[0065] [Concrete batch example #7] According to an exemplary embodiment, a seventh concrete batch example was prepared including the following components: (1) treated perlitic cementitious material, (2) Type 1-2 OPC with standard fineness distribution, (3) sieve sand conforming to ASTM C989 standard, and (4) water. The treated perlitic cementitious material was used at about 50 wt% replacement of the OPC.

[0066] The treated perlitic cementitious material is a mixture of (1) about 93.5 wt% perlite crude with a PSD of D90 of about 38 μm (e.g., Dicalite's DICAPERL® perlite, sourced from New Mexico), (2) about 6 wt% expanded perlite scrap with a PSD of D90 of about 20 μm (e.g., available from Dicalite Management Group, Inc., sourced from Maine, USA), and (3) about 0.5 wt% expanded perlite with a PSD of D90 of about 20 μm (e.g., Imerys' HARBORLITE® thermally expanded perlite). The expanded perlite scrap and expanded perlite are each treated with about 0.15 wt% PVA powder, about 0.3 wt% WEGO Polycarboxylate-PCX, and about 0.05 wt% TEA grinding aid. These materials are mixed together in proportion in one mill and milled (e.g., for about 35 minutes) to a PSD with a D90 of about 38 μm / kg with about 0.15 wt% PVA powder, about 0.3 wt% WEGO Polycarboxylate-PCX, and about 0.05 wt% TEA grinding aid.

[0067] Table 7 below shows the measured compressive strength of several cubes of concrete hardened under conditions conforming to ASTM C989 standard. The compressive strength was determined by breaking the cubes.

[0068] [Table 7]

[0069] [Analysis and Conclusions] The data in Tables 1-7 above generally indicate that perlite crude can be made more reactive without grinding to a fine particle size (e.g., D90 of about 28-38 μm may be sufficient). The data also generally indicate the difference in the results when processing particles with a larger surface area (smaller particle size). Furthermore, the data generally indicate that coating the surface of perlite with PVA powder can help improve the cementitious reaction of perlite crude, while polycarboxylates can help control water consumption and therefore improve flowability. The data also indicate that these reactions can occur in concrete batches using the same processing but with different w / c ratios to obtain good flowability. The data generally indicate that such mixes can reach standard 28-day strengths at or above those achieved with OPC-only mixes, despite the lower w / c ratios. Moreover, the data generally indicates that the use of PVA powder and polycarboxylate materials in combination with mill processing can provide a viable and highly replaceable substitute for other pozzolans (e.g., fly ash, slag, etc.) in the preparation of cementitious materials and concrete. The data also indicates that, at least in some cases, the lightweight nature of the expanded perlite waste can be reduced to approximately 7 lbs. / ft when processed as described herein. 3 From about 12 lbs. / ft 3 The reactivity of the perlite ore increased to 100%, indicating that its reactivity was higher than that of the pearlite ore itself.

[0070] Additionally, testing of perlite for alkali content, as variously described herein, has shown total alkali values ​​in the range of about 6-8%. Alkali-silica reactivity (ASR) testing has shown that less than about 1% (e.g., about 0.5-0.9% or less) of the alkali in the glass matrix is ​​"available". Thus, because class C fly ash has more available alkali than perlite, no issues were found with the material milled to the disclosed D90 particle size when tested for available alkali. In at least some cases, in accordance with some embodiments, the inclusion of a series of additives (e.g., about 0.15-0.3 wt% lithium carbonate / hydroxide milled with perlite ore / glass) may prevent (or reduce) ASR-related issues.

[0071] The description of the exemplary embodiments set forth above has been presented for purposes of illustration and description, and is not intended to be exhaustive or to limit the disclosure to the precise form disclosed. Numerous modifications and variations are possible in light of this disclosure. It is not intended that the scope of the disclosure be limited by this detailed description. Subsequent filed applications that claim priority to this application may claim this disclosed subject matter in different ways and may generally include any set of one or more limitations as variously disclosed or expressly set forth herein.

Claims

1. Perlite crude ore, polyvinyl alcohol (PVA) powder; and a polycarboxylate material. A method for making a treated perlite-based cementitious mixture.

2. 2. The method of claim 1, wherein preparing the treated perlitic cementitious mixture comprises inter-grinding the perlite crude, the PVA powder, and the polycarboxylate material until a D90 particle size distribution of about 38 μm is achieved for the treated perlitic cementitious mixture.

3. 2. The method of claim 1, wherein preparing the treated perlitic cementitious mixture comprises inter-grinding the perlite crude, the PVA powder, and the polycarboxylate material until a D90 particle size distribution of about 28 μm is achieved for the treated perlitic cementitious mixture.

4. The treated perlite-based cementitious mixture further comprises calcium sulfate (CaSO 4 ) and calcium sulfite (CaSO 3 13. The method of claim 1, further comprising at least one of:

5. 5. The method of claim 4, wherein preparing the treated perlite-based cementitious mixture comprises inter-grinding the perlite crude, the PVA powder, the polycarboxylate material, and at least one of the calcium sulfate and calcium sulfite.

6. 10. The method of claim 1, wherein the treated perlite-based cementitious mixture further comprises at least one of expanded perlite waste and expanded perlite.

7. 7. The method of claim 6, wherein preparing the treated perlite-based cementitious mixture comprises inter-grinding the perlite crude, the PVA powder, the polycarboxylate material, and at least one of the expanded perlite waste and the expanded perlite.

8. 10. The method of claim 1, wherein the treated perlite-based cementitious mixture further comprises expanded perlite waste and expanded perlite.

9. 9. The method of claim 8, wherein producing the treated perlite-based cementitious mixture comprises inter-grinding the perlite crude, the PVA powder, the polycarboxylate material, the expanded perlite shavings, and the expanded perlite.

10. The treated perlitic cementitious mixture produced according to any one of claims 1 to 9; Ordinary Portland cement (OPC) and Water, A method of making concrete comprising at least one of rock and sand.

11. 11. The method of claim 10, wherein the treated perlitic cementitious mixture and the OPC are provided in a 50:50 blend.

12. A concrete product comprising the concrete made according to claim 10.

13. Perlite crude ore, Polyvinyl alcohol (PVA) powder; and a polycarboxylate material.

14. 14. The composition of claim 13, wherein the composition has a D90 particle size distribution of about 38 μm±3 μm.

15. 14. The composition of claim 13, wherein the composition has a D90 particle size distribution of about 28 μm±3 μm.

16. The composition of any one of claims 13 to 15, further comprising ordinary portland cement (OPC).

17. 14. The composition of claim 13, further comprising expanded perlite waste.

18. 14. The composition of claim 13 further comprising expanded perlite.

19. 20. The composition of claim 17, wherein the expanded perlite chip has a D90 particle size distribution of about 40 μm.

20. 20. The composition of claim 18, wherein the expanded perlite has a D90 particle size distribution of about 25 μm.

21. 20. The composition of claim 17, wherein the expanded perlite chip has a D90 particle size distribution of about 20 μm.

22. 20. The composition of claim 18, wherein the expanded perlite has a D90 particle size distribution of about 20 μm.

23. Calcium sulfite (CaSO 3 14. The composition of claim 13, further comprising:

24. Calcium sulfate (CaSO 4 14. The composition of claim 13, further comprising: